Few choices : women, work and family - Duffy, Ann (Network basics book., 1989)
Contrary to myth, full-time homemaking is a relatively recent life pattern for married women. Throughout history, women have more typically combined paid labour and family obligations. This book examines the few choices that confront women today in their efforts to balance paid work and family life.